2021
DOI: 10.1111/1744-9987.13762
|View full text |Cite
|
Sign up to set email alerts
|

Poorer clinical outcomes of early‐onset peritonitis in elderly peritoneal dialysis patients: A longitudinal and multicenter study

Abstract: Introduction: Early-onset peritonitis (EOP) is a risk factor for mortality in peritoneal dialysis (PD) patients. This study investigates the clinical features and outcomes of EOP in elderly patients. Methods: This multicenter retrospective study evaluated 433 elderly PD patients with end-stage renal disease. The cohort was divided into nonperitonitis group (n = 239), EOP group (≤12 months, n = 109) and late-onset peritonitis (LOP) group (>12 months, n = 85). Clinical data, treatment results, and outcomes were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…Previous studies of adult patients of all ages undergoing USPD had similar findings [27][28][29]. Our previous study indicated that patients' unskilled PD technique could increase the risk of early-onset peritonitis in elderly patients during the early stage of dialysis [37]. Phang et al [32] suggested that dialysate leakage may increase the risk of peritonitis.…”
Section: Discussionsupporting
confidence: 62%
“…Previous studies of adult patients of all ages undergoing USPD had similar findings [27][28][29]. Our previous study indicated that patients' unskilled PD technique could increase the risk of early-onset peritonitis in elderly patients during the early stage of dialysis [37]. Phang et al [32] suggested that dialysate leakage may increase the risk of peritonitis.…”
Section: Discussionsupporting
confidence: 62%
“…While prior literature has suggested a potential reduction in peritonitis risk in APD patients, our research uncovered a statistically significant difference, with 56.0% of cases occurring in APD compared to 44.0% in CAPD (p < 0.001). The observed variation prompts further inquiry into factors that may contribute to these differences, including patient demographics, adherence to aseptic techniques, and the potential impact of the automated nature of APD [28,29]. Understanding and addressing these nuances in peritonitis risk across peritoneal dialysis modalities is crucial for optimizing patient care and outcomes in the long-term management of end-stage renal disease.…”
Section: Discussionmentioning
confidence: 99%